2007
DOI: 10.1007/s11746-007-1087-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Turkish Quercus L. Taxa Based on Fatty Acid Compositions of the Acorns

Abstract: Total oil content and the composition of fatty acids were analyzed in the acorns of 16 Quercus taxa from Turkey. The range of total fat varied between 0.7 and 7.4%. Oleic (10.2-54.4%), linoleic (24.2-49.1%), palmitic (13.4-30.4%), alpha linolenic (1.5-8.6%) and stearic acid (1.5-4.5%) were major fatty acids for all taxa. Significantly differences at section level were found (p < 0.05) for palmitic, stearic and oleic acid concentration. Saturated (17.0-38.6%), mono unsaturated (11.0-55.5%) and unsaturated fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 20 publications
0
28
0
1
Order By: Relevance
“…Several studies have reported that the oil content of various white species of Quercus, did not exceed 12% (Rababah et al, 2008;Bernardo-Gil, 2007;Özcan, 2007;León-Camacho et al, 2004;M'Hrit et al, 1998), which indicates that acorn oil cannot be considered as commercial edible oil, BernardoGil et al, (2007) reported that the Portuguese legislation classified the acorn oil as an alimentary oil, although no industrial oil has been produced. However, some of Q. Erthrobalanus spp.…”
Section: Tocopherols Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that the oil content of various white species of Quercus, did not exceed 12% (Rababah et al, 2008;Bernardo-Gil, 2007;Özcan, 2007;León-Camacho et al, 2004;M'Hrit et al, 1998), which indicates that acorn oil cannot be considered as commercial edible oil, BernardoGil et al, (2007) reported that the Portuguese legislation classified the acorn oil as an alimentary oil, although no industrial oil has been produced. However, some of Q. Erthrobalanus spp.…”
Section: Tocopherols Analysismentioning
confidence: 99%
“…(black and red oak group) contain 30.8-31.3% oil, being similar to or higher than the best oil olives (Ofcarcik, 1971). In addition, acorn oils have good nutritional quality with a flavor comparable to that of olive oil (Özcan, 2007;Lopes et al, 2005;Bainbridge, 1986). It has been reported that the oleic acid and linoleic acid content in 16 acorns of Quercus taxa from Turkey were between 53-65% and 24.2-49.1%, respectively (Özcan, 2007).This justifies the fact that acorn oil should enjoy the respect of dietary reference for fatty acid intake, particularly linoleic acid, which is considered the most significant and valuable benefit to human health (Horrobin, 1983).…”
Section: Tocopherols Analysismentioning
confidence: 99%
“…It could be generally said that 31-55 % of their mass is composed by starch, 2.75-8.44 % protein (with advantageous amino acid composition, and high content of essential amino acids, proper especially for adults), 0.7-9 % fat (although in some species of Quercus Erthrobalanus spp., i.e., black and red oak group, it may exceed 31 %) [11,[15][16][17]. Oil present in acorns has a taste comparable to olive oil and contains high levels of unsaturated fatty acids (even above 80 %), mostly oleic and linoleic acids, 10.2-65 % and 17.6-49.1 %, respectively [15,18]. Acorns are also a good source of minerals and biologically active compounds with an antioxidant status, which allows treating them as functional food [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Variations in fatty acid levels were observed in different Quercus spp. taxas (Charef et al 2008;Ö zcan 2007). Fatty acid profiles were affected by intra-annual and inter-annual time sampling (Tejerina et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we continue our efforts to characterize the morphometry and chemical composition from the acorns of thirteen Andalusia Holm oak populations. Acorn chemical composition of oaks has shown a valuable tool for assessing variability Ö zcan 2007;Rafii et al 1991Rafii et al , 1993, but few studies have been carried out on acorn chemical composition of Andalusia Holm oak acorns from a natural variability point of view (Rodríguez-Estévez et al 2009;Valero et al 2011). Chemosystematic differentiation based on differences in acorn fatty acid composition between Italian and Spanish populations of Q. ilex and Q. rotundifolia yielded partial separations of the individual populations (Rafii et al 1991).…”
Section: Introductionmentioning
confidence: 99%